A cloud-based JupyterHub platform for community research with the NextGen water resources modeling framework - Ayman Nassar; David G. Tarboton; Furqan Baig; Josh Cunningham; Arpita Patel; James Halgren; Benjamin Lee; Homa Salehabadi; Anthony M. Castronova; Irene Garousi-Nejad (Environmental Modelling & Software, 2026)

Control of fall armyworm with Spodoptera frugiperda multiple nucleopolyhedrovirus in sweet corn cultivated under agroecological conditions - T. Cunningham; C. de la Colina; M. Pérez; G. Quintana; Marco D´Amico; M. Berretta; J. Niz; M. L. Ferrelli; R. Salvador (BioControl, 2026)

The Sedimentary Geochemistry and Paleoenvironments Project Phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

The behavioural, toxicological, and biochemical effects of caffeine on Lumbriculus variegatus - Grace E. Labdon; Roisin Kelly-Laubscher; Margaret R. Cunningham; Nia A. Davies; Sophie G. Reed; Aidan Seeley (Environmental Toxicology and Pharmacology, 2026)

Shelters of Necessity: Exploring the Geoheritage of Dugout Architecture in Early Northwest Texas Settlement - Glenn G. Fernández-Céspedes; Stance Hurst; Doug Cunningham; Emily Ladd; Eileen Johnson (Geoheritage, 2026)
This study explores the geoheritage significance of dugouts constructed by early Anglo-American settlers across the Southern High Plains and Rolling Plains of Texas. Geoheritage, which in this study emphasizes the relationship between geodiversity and cultural adaptation, provides a framework to examine how settlers used locally available geological resources for shelter in response to environmental challenges. Fieldwork and archival research has documented 11 dugouts from buffalo hunters, cattle ranchers, sheepherders, and homesteaders. Analysis includes Geographic Information Systems (GIS) and photogrammetric modeling to evaluate the impact of geodiversity on dugout placement, construction materials, and design. Results reveal that most dugouts were constructed near critical resources such as water sources and rock outcrops, with sandstone from the Dockum Group being the most commonly used building material. Terrain sheltered from wind is prioritized, with 64% of dugouts located on slopes or near valleys, highlighting strategic responses to the Southern Plains climate. The variability in dugout dimensions and materials among cultural groups underscores the diverse ways settlers interacted with available resources, reflecting both immediate needs and cultural practices. This research advances geoheritage by demonstrating that even temporary, adaptive structures like dugouts contribute to the understanding of human interaction with geodiversity. By situating these shelters within a geoheritage framework, the study provides new insights into how early settlers adapted to and modified their landscapes, adding depth to the region’s cultural and geological legacy. The findings support a more inclusive view of geoheritage, encompassing permanent and transient human imprints on the landscape.

Drought and reservoir drawdown: implications for bull trout distribution and passage - Blake R. Hamilton; Connor D. Cunningham; Brittany A. Beebe; Craig A. Haskell; Jason G. Romine (Environmental Biology of Fishes, 2026)

The Sedimentary geochemistry and paleoenvironments project phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Forward osmosis followed by reverse osmosis for the removal of contaminants of emerging concern using a CO2-responsive draw agent - Rachel S. Korchinsky; José Giovanni L. Brito; Louis Fieldhouse; Pascale Champagne; Michael F. Cunningham; Philip G. Jessop (Journal of Hazardous Materials, 2025)

Population Genomics and the Environmental Drivers of Population Structure in a Cosmopolitan Marine Predator, Tursiops truncatus - Daniel M. Moore; Andre E. Moura; Ada Natoli; Elena Papale; Emily G. Cunningham; Mónica A. Silva; Tilen Genov; Stefania Gaspari; Giuseppa Buscaino; Per Berggren; Darren R. Gröcke; A. Rus Hoelzel (Molecular Ecology, 2025)
The marine environment comprises vast regions without physical barriers to movement, making the understanding of population isolation and the evolution of diversity challenging. This is especially the case for highly mobile marine species. Here we investigate populations of the common bottlenose dolphin ( Tursiops truncatus ) across the Mediterranean Sea and adjacent North Atlantic using high‐resolution genomic markers (RADseq) and stable isotope analyses to better understand the evolution of population structure in this system. High‐resolution genomic data and broad geographic sampling revealed patterns of structure not previously identified, and integration with stable isotope data suggests that prey choice varies across this region. Unexpected patterns included genetic and isotopic similarity between the North Atlantic and the region around Sicily (but not including the medially located Gulf of Cádiz and surrounding regions). The regional habitat within and beyond the Mediterranean Sea is structured with ocean frontal systems including thermal and halocline transitions, several of which show alignment with genetic transitions within our data. Our data help to distinguish among possible drivers of population differentiation for a marine predator that has the potential for long‐distance dispersion.

Drivers and Dynamics of Salmon Bycatch in the Eastern Bering Sea Pollock Fishery - Lukas B. DeFilippo; Wesley A. Larson; Patrick D. Barry; Curry J. Cunningham; Joseph A. Langan; Sabrina Garcia; Kathrine G. Howard; James N. Ianelli; Diana L. Stram (Fish and Fisheries, 2025)
Minimising bycatch is a pervasive challenge for sustainable fisheries management, the importance of which is amplified for non‐target species or populations that are in decline. In the eastern Bering Sea (EBS) walleye pollock ( Gadus chalcogrammus ) fishery, salmon—most notably Chinook ( Oncorhynchus tshawytscha ) and chum ( O. keta )—are encountered as bycatch. Salmon bycatch in the EBS pollock fishery has become an issue of growing concern, largely due to declines in Western Alaska Chinook and chum salmon, which support directed fisheries vital to the wellbeing of regional communities. Consequently, minimising salmon bycatch is a management priority and requires information on the underlying processes driving encounters between salmon and pollock vessels. In this study, we present a broad synthesis of Chinook and chum salmon bycatch dynamics in the EBS pollock fishery. Applying a hierarchical modelling framework to nearly 120,000 catch records collected over 13 years (2011–2023), we quantify patterns of variation in salmon bycatch over space and time, and environmental drivers thereof. Our results reveal spatially structured, interannual variation in chum and Chinook salmon bycatch associated with oceanographic conditions. We also demonstrate the importance of interactions between bottom depth and local sea surface temperature anomalies in shaping bycatch rates, which vary across fishing seasons and salmon species. By advancing our understanding of the factors that contribute to encounters between pollock vessels and salmon, this study can inform ongoing management efforts aimed at minimising multispecies salmon bycatch in a changing marine ecosystem.

Brain anatomy of a clonal fish, the Amazon Molly (Poecilia formosa): effects of early-life environment - Hayo G. Nadema; Tyler J. Reich; Eline J. E. Weenink; Debbie Cunningham; Elvis Wong; Ingo Schlupp; Alexander Kotrschal (Evolutionary Ecology, 2025)
During ontogeny, environmental factors can shape trait development and resource allocation to aid survival, reflecting adaptive plasticity. This may include differential investment in brain regions in response to cognitive challenges. Especially the brain anatomy of fish seems to respond readily to biotic and abiotic factors. However, we currently lack sufficient data to determine the extent to which such changes are consistent across species. To extend the phylogenetic breadth in this endeavour, we studied how brain anatomy of Amazon mollies ( Poecilia formosa ) responds to the presence or absence of physical enrichment and/or visual neighbours. The Amazon molly is a clonal species and genetically highly uniform, so that differences in brain anatomy of individuals from the same clonal lineage are most likely due to the environmental conditions provided, rather than inherent genetic differences. We quantified brain anatomy by determining the volumes of six main brain regions (olfactory bulb; telencephalon; optic tectum; cerebellum; dorsal medulla; hypothalamus) and overall brain size. While brain anatomy was overall unaffected by the visual presence of a conspecific, we found that the cerebellum was larger in animals reared in an environmentally complex habitat. Our results corroborate the idea that use of certain cognitive domains fosters enlargement in the region governing those.

A Review of Methionine and Cysteine: Their Roles as Sinks for Reactive Oxygen and Nitrogen Species, Including Bioinformatic Analysis of Their Percent Compositions in Metabolic Proteins - Bethany F. Laatsch; Burhan A. Ali; Anna R. Berthiaume; Grace C. Cunningham; Sabrina M. Duncan; Nathan Hau; Audrey Ho; Marais A. Loomis; Harrison R. Lowater; Brenya L. McNally; Kate L. Mueller; Matt Poppitz; et al. (Indian Journal of Clinical Biochemistry, 2025)

The psychedelic (−)-2,5-dimethoxy-4-iodoamphetamine [(−)-DOI] demonstrates efficacy in reducing cocaine reward and motivation in male rats - Leah M. Salinsky; Christina R. Merritt; Erik J. Garcia; Robert G. Fox; Joshua C. Zamora; Noelle C. Anastasio; Kathryn A. Cunningham (Psychopharmacology, 2025)
Rationale and objectives Overdose fatalities involving cocaine continue to rise with over 5.3 million cocaine users reported in the United States in 2022. The abuse liability of cocaine is reliant upon inhibition of dopamine ( DA ) reuptake and consequent increase in DA efflux in meso-corticolimbic circuitry that controls reward and motivation. Cocaine also increases serotonin ( 5-HT ) efflux which is integral in cocaine abuse. The 5-HT 2A receptor ( 5-HT 2A R ) is a key regulator of meso-corticolimbic DA release and controls cellular mechanisms underlying cocaine effects. 5-HT 2A R actions contribute importantly to psychedelic mechanisms of action, and the efficacy of these compounds in limiting cocaine intake is unknown. The present studies evaluated the efficacy of acute administration of a psychedelic to reduce cocaine intake using standard and advanced preclinical models of drug self-administration. Methods Both a standard fixed ratio ( FR ) schedule and behavioral economics threshold procedure of cocaine intravenous self-administration were employed to evaluate the efficacy of the psychedelic 5-HT 2A R agonist (−)-2,5-dimethoxy-4-iodoamphetamine [ ( − )-DOI ] to decrease cocaine intake and motivation for cocaine in male rats. The 5-HT 2A R-selective antagonist M100907 was utilized to explore the role of 5-HT 2A R in the effects of (−)-DOI on cocaine intake. Results We found that (−)-DOI dose-dependently reduced intake on the FR5 schedule of cocaine IVSA and left shifted the demand curve to evoke greater sensitivity to price increases in the behavioral economics paradigm. Pretreatment with M100907 abated the efficacy of (−)-DOI on cocaine intake in both paradigms. Conclusion (−)-DOI ‘devalued’ cocaine reward and motivation to take cocaine in a 5-HT 2A R-dependent manner. As serotonergic psychedelics emerge as therapeutic candidates, investigations of 5-HT 2A R-acting psychedelics in preclinical analyses of cocaine intake and relapse vulnerability during abstinence will be valuable as prelude to future clinical trials.

Variety-seeking behavioral markers in an immersive virtual reality food buffet are associated with greater food and energy intake in laboratory meals - John W. Long; Paige M. Cunningham; Sara J. Maksi; Kathleen L. Keller; Charissa S.L. Cheah; Lee Boot; Alexander Klippel; Timothy R. Brick; Caitlyn G. Edwards; Janelle Kort; Paige Grabusky; Barbara J. Rolls; et al. (Appetite, 2025)

Spatiotemporal drivers of rodenticide exposure in a mammalian forest carnivore - Stephanie A. Cunningham; Jacqueline L. Frair; Paul G. Jensen; Krysten L. Schuler (Science of The Total Environment, 2025)

Escalating threats: house mouse attacks on adult wandering albatrosses spread across Marion Island - Michelle M. Risi; Christopher W. Jones; Maëlle Connan; Rhiannon Gill; Vanessa Stephen; Susan J. Cunningham; Peter G. Ryan (Biological Invasions, 2025)

Quantifying taxon-specific habitat connectivity requirements of urban wildlife using structured expert judgement - Stephanie K. Courtney Jones; Luke S. O'Loughlin; Danswell Starrs; Jacinta E. Humphrey; Stephanie A. Pulsford; Hugh Allan; Matt Beitzel; Kym Birgen; Suzi Bond; Jenny Bounds; Deborah Bower; Renee Brawata; et al. (Biological Conservation, 2025)

Forecasting drought using machine learning: a systematic literature review - Ricardo S. Oyarzabal; Leonardo B. L. Santos; Christopher Cunningham; Elisangela Broedel; Glauston R. T. de Lima; Gisleine Cunha-Zeri; Jerusa S. Peixoto; Juliana A. Anochi; Klaifer Garcia; Lidiane C. O. Costa; Luana A. Pampuch; Luz Adriana Cuartas; et al. (Natural Hazards, 2025)

Test of Rapamycin in Aging Dogs (TRIAD): study design and rationale for a prospective, parallel-group, double-masked, randomized, placebo-controlled, multicenter trial of rapamycin in healthy middle-aged dogs from the Dog Aging Project - Amanda E. Coleman; Kate E. Creevy; Rozalyn Anderson; May J. Reed; Virginia R. Fajt; Kathleen M. Aicher; Genna Atiee; Brian G. Barnett; Ryan D. Baumwart; Beth Boudreau; Suzanne M. Cunningham; Matthew D. Dunbar; et al. (GeroScience, 2025)

A Conceptual Framework for Measuring Ecological Novelty - Timothy L. Staples; Jessica Blois; Katie L. Cramer; Emer T. Cunningham; Maria Dornelas; Simon G. Haberle; Tina Heger; Wolfgang Kiessling; Anne E. Magurran; Aaron O'Dea; Amelia M. Penny; Volker C. Radeloff; et al. (Global Ecology and Biogeography, 2025)
Background Human pressures are driving the emergence of unprecedented, ‘novel’, ecological and environmental systems. The concept of novel (eco)systems is well accepted by the scientific community, but the use and measurement of novelty has outgrown initial definitions and critiques. There are still unresolved methodological and conceptual differences in quantifying novelty that prevent a unified research approach. Framework Here we present a conceptual framework and guidelines to unify past and future measurement of ecological novelty. Under this framework, novelty is a property of an ecological or environmental entity of interest. Novelty is quantified as the comparison between the target entity and a reference set, measured as the summary of degrees of difference across one or more dimensions. Choices in these components, particularly the reference set, can change resulting novelty measurements and inferences. Showcase We provide a case‐study to showcase our framework, measuring pre‐ and post‐European novelty in 99 pollen assemblages in Midwest USA forests. We paired this quantitative exploration with a five‐step process designed to improve the utility and outcomes of novelty analyses. Conclusions Quantitative novelty has immense value in studies of abrupt ecological change, linking climatic and ecological change, biotic interactions and invasions, species range shifts and fundamental theories. Our framework offers a unified overview and is also primed for integration into management and restoration workflows, providing consistent and robust measurements of novelty to support decision making, priority setting and resource allocation.

Establishing the limitations on using archived marine mammal samples for stable isotope analysis: an examination of differing preservation methods on tissues of harbor porpoise ( Phocoena phocoena ) and gray seal ( Halichoerus grypus ) - Daniel M. Moore; Emily G. Cunningham; Kayla D. Crowder; Darren R. Gröcke (Marine Mammal Science, 2025)
The use of biological samples from museum and/or archive collections is common in stable isotope research, particularly for marine mammals. Yet, the temporal stability of isotopic values across various tissue types and the influence of different preservatives on these values are not fully understood, posing significant challenges for accurate data interpretation. Here we examine the impact of three different tissue preservation methods (DMSO, ethanol, freezing), on seven different tissues (blubber, heart, kidney, lung, liver, muscle, and skin) from both a harbor porpoise ( Phocoena phocoena ) and a gray seal ( Halichoerus grypus ) for stable isotope analysis in a 1‐year period. Our results demonstrate that storage in DMSO generates greater temporal variability in δ 13 C and δ 15 N for all tissue types, particularly in the first six months of storage. Furthermore, tissues stored in DMSO often exhibited lower δ13C and δ15N values compared to those stored frozen or in ethanol. This finding highlights a significant issue for studies utilizing tissues stored in DMSO, regardless of the storage duration. These results underscore the critical need for careful consideration of preservation methods in studies involving stored tissues, providing valuable insights for experimental design and management of tissue archives.

Land Use Change Consistently Reduces α‐ But Not β‐ and γ‐Diversity of Bees - Toby P. N. Tsang; A. A. Amado De Santis; Gabriela Armas‐Quiñonez; John S. Ascher; Eva Samanta Ávila‐Gómez; András Báldi; Kimberly M. Ballare; Mario V. Balzan; Weronika Banaszak‐Cibicka; Svenja Bänsch; Yves Basset; Adam J. Bates; et al. (Global Change Biology, 2025)
Land use change threatens global biodiversity and compromises ecosystem functions, including pollination and food production. Reduced taxonomic α‐diversity is often reported under land use change, yet the impacts could be different at larger spatial scales (i.e., γ‐diversity), either due to reduced β‐diversity amplifying diversity loss or increased β‐diversity dampening diversity loss. Additionally, studies often focus on taxonomic diversity, while other important biodiversity components, including phylogenetic diversity, can exhibit differential responses. Here, we evaluated how agricultural and urban land use alters the taxonomic and phylogenetic α‐, β‐, and γ‐diversity of an important pollinator taxon—bees. Using a multicontinental dataset of 3117 bee assemblages from 157 studies, we found that taxonomic α‐diversity was reduced by 16%–18% in both agricultural and urban habitats relative to natural habitats. Phylogenetic α‐diversity was decreased by 11%–12% in agricultural and urban habitats. Compared with natural habitats, taxonomic and phylogenetic β‐diversity increased by 11% and 6% in urban habitats, respectively, but exhibited no systematic change in agricultural habitats. We detected a 22% decline in taxonomic γ‐diversity and a 17% decline in phylogenetic γ‐diversity in agricultural habitats, but γ‐diversity of urban habitats was not significantly different from natural habitats. These findings highlight the threat of agricultural expansions to large‐scale bee diversity due to systematic γ‐diversity decline. In addition, while both urbanization and agriculture lead to consistent declines in α‐diversity, their impacts on β‐ or γ‐diversity vary, highlighting the need to study the effects of land use change at multiple scales.

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Russian olive distribution and invasion dynamics along the Powder River, Montana and Wyoming, USA - Karissa Courtney; Catherine Buczek; Sharon Bywater-Reyes; Dahlia Shahin; Amy Tian; Carly Andrews; Scott Franklin; Brian Woodward; Scott Cunningham; Anthony G. Vorster (Biological Invasions, 2024)
The invasive shrub, Russian olive ( Elaeagnus augustifolia ), is widely established within riparian areas across North America and eastern Europe. Limited information on its distribution and invasion dynamics in northern regions has hampered understanding and management efforts. Given this lack of spatial and ecological information we worked with local stakeholders and developed two main objectives: (1) map the distribution of Russian olive along the Powder River (Montana and Wyoming, United States) as of 2020 with field data and remote sensing; and (2) relate that distribution to environmental variables to understand its habitat suitability and community/invasion dynamics. Field data showed Russian olive has reached near equal canopy cover (18.3%) to native Plains cottonwood ( Populus deltoides; 19.1%) and has a broader distribution. At the watershed scale, we modeled Russian olive distribution using field surveys, ocular sampling of aerial imagery, and spectral variables from Sentinel-2 MultiSpectral Instrument using a random forest model (RMSE = 15.42, R 2 = 0.64). A statistical model linking the resulting Russian olive percent cover detection map to environmental variables for the entire watershed indicated Russian olive cover increased with flow accumulation and decreased with elevation, and was associated with poorer soil types. We attribute the success of Russian olive to its broad habitat suitability combined with changing hydrologic conditions favoring it over natives. The maps of Russian olive cover along the Powder River and its main tributaries in northern Wyoming and southern Montana revealed regions of the watershed with high and low cover, which can guide landscape-scale management prioritization. This study provides a repeatable Russian olive detection method due to the use of Sentinel-2 imagery that is available worldwide and provides insight into Russian olive’s ecological relationships and success with relevance for management across areas with similar environmental conditions.

Body size and early marine conditions drive changes in Chinook salmon productivity across northern latitude ecosystems - Megan L. Feddern; Rebecca Shaftel; Erik R. Schoen; Curry J. Cunningham; Brendan M. Connors; Benjamin A. Staton; Al von Finster; Zachary Liller; Vanessa R. von Biela; Katherine G. Howard (Global Change Biology, 2024)
Disentangling the influences of climate change from other stressors affecting the population dynamics of aquatic species is particularly pressing for northern latitude ecosystems, where climate‐driven warming is occurring faster than the global average. Chinook salmon ( Oncorhynchus tshawytscha ) in the Yukon‐Kuskokwim (YK) region occupy the northern extent of their species' range and are experiencing prolonged declines in abundance resulting in fisheries closures and impacts to the well‐being of Indigenous people and local communities. These declines have been associated with physical (e.g., temperature, streamflow) and biological (e.g., body size, competition) conditions, but uncertainty remains about the relative influence of these drivers on productivity across populations and how salmon–environment relationships vary across watersheds. To fill these knowledge gaps, we estimated the effects of marine and freshwater environmental indicators, body size, and indices of competition, on the productivity (adult returns‐per‐spawner) of 26 Chinook salmon populations in the YK region using a Bayesian hierarchical stock‐recruitment model. Across most populations, productivity declined with smaller spawner body size and sea surface temperatures that were colder in the winter and warmer in the summer during the first year at sea. Decreased productivity was also associated with above average fall maximum daily streamflow, increased sea ice cover prior to juvenile outmigration, and abundance of marine competitors, but the strength of these effects varied among populations. Maximum daily stream temperature during spawning migration had a nonlinear relationship with productivity, with reduced productivity in years when temperatures exceeded thresholds in main stem rivers. These results demonstrate for the first time that well‐documented declines in body size of YK Chinook salmon were associated with declining population productivity, while taking climate into account.

Addressing the Boundary and Modifiable Areal Unit Problems Simultaneously when Measuring Landscape Fragmentation Using Patch-Based Metrics: a Case Study of Effective Mesh Size in Nova Scotia, Canada - Caitlin Cunningham; Karen F. Beazley; Peter G. Bush; John C. Brazner (Environmental Modeling & Assessment, 2024)

Unit size influences ad libitum intake in a snacking context via eating rate - Madeline M. Harper; Paige M. Cunningham; Ciarán G. Forde; John E. Hayes (Appetite, 2024)

Predicting energy consumption of zero emission buses using route feature selection methods - L.A.W. Blades; T. Matthews; T.E. McGrath; J. Early; G. Cunningham; A. Harris (Transportation Research Part D: Transport and Environment, 2024)

First report of Ornithogalum virus 3 in Galtonia candicans in the United Kingdom - J Dixon; K Chisnall; M Mynett; C Cunningham; G Webster; A Skelton; A. R. Fowkes; A Fox (Journal of Plant Pathology, 2023)

A trait-based assessment of southern African arid-zone birds' vulnerability to climate change - Stephanie L. Payne; Susan J. Cunningham; Caroline G. Howes; Andrew E. McKechnie (Biological Conservation, 2023)

The transport and fate of microplastic fibres in the Antarctic: The role of multiple global processes - Eoghan M. Cunningham; Nuria Rico Seijo; Katye E. Altieri; Riesna R. Audh; Jessica M. Burger; Thomas G. Bornman; Sarah Fawcett; Claire M. B. Gwinnett; Amy O. Osborne; Lucy C. Woodall (Frontiers in Marine Science, 2022)
Understanding the transport and accumulation of microplastics is useful to determine the relative risk they pose to global biodiversity. The exact contribution of microplastic sources is hard to elucidate; therefore, investigating the Antarctic Weddell Sea, an area known for its remoteness and little human presence (i.e. limited pollution sources), will help us to better understand microplastic transportation. Here, we investigate the presence of microplastics in a range of Antarctic sample media including air, seawater, and sediment. We hypothesised that multiple transportation processes including atmospheric and oceanic vectors determine the presence of microplastics in the Antarctic. Using techniques including Polarised Light Microscopy and Raman Spectrometry, we identified mostly fibres and categorised them based on their optical and chemical properties. A total of 47 individual microplastic categories (45 of which were fibres) were identified in the air, seawater, and sediment samples. The majority of categories did not overlap multiple media (42/47); however, four fibre categories were present in both air and water samples, and another fibre category was found in all three media (category 27). We suggest that the large variety of fibres identified and the overlap of fibre categories among media indicates that the pollution may result from multiple diffuse sources and transportation pathways. Additionally, our Air Mass Back Trajectory analyses demonstrates that microplastic fibres are being transported by air masses or wind, and strongly suggests that they are transported to the Antarctic from southern South America. We also propose that fibres may be transported into the Antarctic in subsurface waters, and as pollution was identified in our sediment and additional sea ice samples, we suggest that the coastal and Antarctic deep sea may be a sink for microplastic fibres. The results shown here from a remote, near-pristine system, further highlight the need for a global response to the plastic pollution crisis.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

CropPol : A dynamic, open and global database on crop pollination - Alfonso Allen‐Perkins; Ainhoa Magrach; Matteo Dainese; Lucas A. Garibaldi; David Kleijn; Romina Rader; James R. Reilly; Rachael Winfree; Ola Lundin; Carley M. McGrady; Claire Brittain; David J. Biddinger; et al. (Ecology, 2022)
Seventy five percent of the world's food crops benefit from insect pollination. Hence, there has been increased interest in how global change drivers impact this critical ecosystem service. Because standardized data on crop pollination are rarely available, we are limited in our capacity to understand the variation in pollination benefits to crop yield, as well as to anticipate changes in this service, develop predictions, and inform management actions. Here, we present CropPol, a dynamic, open, and global database on crop pollination. It contains measurements recorded from 202 crop studies, covering 3,394 field observations, 2,552 yield measurements (i.e., berry mass, number of fruits, and fruit density [kg/ha], among others), and 47,752 insect records from 48 commercial crops distributed around the globe. CropPol comprises 32 of the 87 leading global crops and commodities that are pollinator dependent. Malus domestica is the most represented crop (32 studies), followed by Brassica napus (22 studies), Vaccinium corymbosum (13 studies), and Citrullus lanatus (12 studies). The most abundant pollinator guilds recorded are honey bees (34.22% counts), bumblebees (19.19%), flies other than Syrphidae and Bombyliidae (13.18%), other wild bees (13.13%), beetles (10.97%), Syrphidae (4.87%), and Bombyliidae (0.05%). Locations comprise 34 countries distributed among Europe (76 studies), North America (60), Latin America and the Caribbean (29), Asia (20), Oceania (10), and Africa (7). Sampling spans three decades and is concentrated on 2001–2005 (21 studies), 2006–2010 (40), 2011–2015 (88), and 2016–2020 (50). This is the most comprehensive open global data set on measurements of crop flower visitors, crop pollinators and pollination to date, and we encourage researchers to add more datasets to this database in the future. This data set is released for non‐commercial use only. Credits should be given to this paper (i.e., proper citation), and the products generated with this database should be shared under the same license terms (CC BY‐NC‐SA).

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Testing a global standard for quantifying species recovery and assessing conservation impact - Molly K. Grace; H. Resit Akçakaya; Elizabeth L. Bennett; Thomas M. Brooks; Anna Heath; Simon Hedges; Craig Hilton‐Taylor; Michael Hoffmann; Axel Hochkirch; Richard Jenkins; David A. Keith; Barney Long; et al. (Conservation Biology, 2021)
Recognizing the imperative to evaluate species recovery and conservation impact, in 2012 the International Union for Conservation of Nature (IUCN) called for development of a “Green List of Species” (now the IUCN Green Status of Species). A draft Green Status framework for assessing species’ progress toward recovery, published in 2018, proposed 2 separate but interlinked components: a standardized method (i.e., measurement against benchmarks of species’ viability, functionality, and preimpact distribution) to determine current species recovery status (herein species recovery score ) and application of that method to estimate past and potential future impacts of conservation based on 4 metrics ( conservation legacy, conservation dependence , conservation gain , and recovery potential ). We tested the framework with 181 species representing diverse taxa, life histories, biomes, and IUCN Red List categories (extinction risk). Based on the observed distribution of species’ recovery scores, we propose the following species recovery categories : fully recovered, slightly depleted, moderately depleted, largely depleted, critically depleted, extinct in the wild, and indeterminate. Fifty‐nine percent of tested species were considered largely or critically depleted. Although there was a negative relationship between extinction risk and species recovery score, variation was considerable. Some species in lower risk categories were assessed as farther from recovery than those at higher risk. This emphasizes that species recovery is conceptually different from extinction risk and reinforces the utility of the IUCN Green Status of Species to more fully understand species conservation status. Although extinction risk did not predict conservation legacy, conservation dependence, or conservation gain, it was positively correlated with recovery potential. Only 1.7% of tested species were categorized as zero across all 4 of these conservation impact metrics , indicating that conservation has, or will, play a role in improving or maintaining species status for the vast majority of these species. Based on our results, we devised an updated assessment framework that introduces the option of using a dynamic baseline to assess future impacts of conservation over the short term to avoid misleading results which were generated in a small number of cases, and redefines short term as 10 years to better align with conservation planning. These changes are reflected in the IUCN Green Status of Species Standard.

Ordovician volcanic rocks record rifting, Variscan metamorphism and gold mineralization processes (Truchas Syncline, NW Iberia, Spain) - L. González-Menéndez; F. Gómez-Fernández; J. K. Cunningham; S. Menéndez; P. Caldevilla; G. Gallastegui; A. Cuesta (Journal of Iberian Geology, 2021)

Quantifying 25 years of disease‐caused declines in Tasmanian devil populations: host density drives spatial pathogen spread - Calum X. Cunningham; Sebastien Comte; Hamish McCallum; David G. Hamilton; Rodrigo Hamede; Andrew Storfer; Tracey Hollings; Manuel Ruiz‐Aravena; Douglas H. Kerlin; Barry W. Brook; Greg Hocking; Manna E. Jones (Ecology Letters, 2021)
Infectious diseases are strong drivers of wildlife population dynamics, however, empirical analyses from the early stages of pathogen emergence are rare. Tasmanian devil facial tumour disease (DFTD), discovered in 1996, provides the opportunity to study an epizootic from its inception. We use a pattern‐oriented diffusion simulation to model the spatial spread of DFTD across the species' range and quantify population effects by jointly modelling multiple streams of data spanning 35 years. We estimate the wild devil population peaked at 53 000 in 1996, less than half of previous estimates. DFTD spread rapidly through high‐density areas, with spread velocity slowing in areas of low host densities. By 2020, DFTD occupied >90% of the species' range, causing 82% declines in local densities and reducing the total population to 16 900. Encouragingly, our model forecasts the population decline should level‐off within the next decade, supporting conservation management focused on facilitating evolution of resistance and tolerance.

Projected changes in Brook Trout and Brown Trout distribution in Wisconsin streams in the mid-twenty-first century in response to climate change - Matthew G. Mitro; John D. Lyons; Jana S. Stewart; Paul K. Cunningham; Joanna D. T. Griffin (Hydrobiologia, 2019)

Atlantic Meridional Overturning Circulation: Observed Transport and Variability - Eleanor Frajka-Williams; Isabelle J. Ansorge; Johanna Baehr; Harry L. Bryden; Maria Paz Chidichimo; Stuart A. Cunningham; Gokhan Danabasoglu; Shenfu Dong; Kathleen A. Donohue; Shane Elipot; Patrick Heimbach; N. Penny Holliday; et al. (Frontiers in Marine Science, 2019)

Thioredoxin overexpression in both the cytosol and mitochondria accelerates age-related disease and shortens lifespan in male C57BL/6 mice - Geneva M. Cunningham; Lisa C. Flores; Madeline G. Roman; Christie Cheng; Sara Dube; Colton Allen; Joseph M. Valentine; Gene B. Hubbard; Yidong Bai; Thomas L. Saunders; Yuji Ikeno (GeroScience, 2018)

The effect of motor overflow on bimanual asymmetric force coordination - David A. Cunningham; Sarah M. Roelle; Didier Allexandre; Kelsey A. Potter-Baker; Vishwanath Sankarasubramanian; Jayme S. Knutson; Guang H. Yue; Andre G. Machado; Ela B. Plow (Experimental Brain Research, 2017)

The effect of iron limitation on cyanobacteria major nutrient and trace element stoichiometry - Brady R. Cunningham; Seth G. John (Limnology and Oceanography, 2017)
Phytoplankton elemental stoichiometry provides a window into the interactions between marine nutrient distributions and phytoplankton growth. Here, we report the extended elemental stoichiometry of two non‐diazotrophic cyanobacteria strains, Synechococcus WH7803 and Prochlorococcus MED4, in both Fe‐replete and Fe‐deplete media. Fe concentrations were reduced by two orders of magnitude in the Fe‐deplete media, causing growth rates to decline by 38% and 24%, respectively. The average elemental composition of Fe‐replete cells was (C 76.5 N 19 P 1 ) 1000 Fe 52.5 Mn 1.90 Zn 0.86 Cu 0.40 Ni 0.40 Co 0.05 Cd 0.0020 , while Fe‐limited cells averaged (C 121 N 30 P 1 ) 1000 Fe 12.2 Mn 3.22 Zn 1.70 Cu 0.41 Ni 0.36 Co 0.11 Cd 0.0038 The trace‐metal stoichiometries measured here are similar to the ranges previously measured for a strain of Synechococcus and for many species of large eukaryotic phytoplankton. In contrast to large eukaryotic phytoplankton, which have previously exhibited either unchanged or decreased N : P under Fe‐limited conditions, Synechococcus and Prochlorococcus increased N : P in Fe‐deplete media by 58% and 67%, respectively. Previous studies have examined the direct role of Fe in limiting nitrogen fixation by diazotrophs, but this study suggests a second mechanism by which Fe may impact nutrient cycling, by influencing the N : P uptake ratio of non‐diazotrophic cyanobacteria. A model of cyanobacteria distribution and Fe limitation is combined with the N : P stoichiometries measured here to suggest that up to 40% of the particulate organic nitrogen in the surface ocean might be associated with Fe‐limited waters, with the strongest effect observed in the Prochlorococcus dominated subtropical Pacific. Thus, if the effect on N : P we observe in culture is widespread in the oceans it would mean that Fe‐limitation could play a major role in global nitrogen and carbon cycling.

Clinostomum album n. sp. and Clinostomum marginatum (Rudolphi, 1819), parasites of the great egret Ardea alba L. from Mississippi, USA - Thomas G. Rosser; Neely R. Alberson; Ethan T. Woodyard; Fred L. Cunningham; Linda M. Pote; Matt J. Griffin (Systematic Parasitology, 2017)

Assessing the genetic architecture of epithelial ovarian cancer histological subtypes - Gabriel Cuellar-Partida; Yi Lu; Suzanne C. Dixon; Peter A. Fasching; Alexander Hein; Stefanie Burghaus; Matthias W. Beckmann; Diether Lambrechts; Els Van Nieuwenhuysen; Ignace Vergote; Adriaan Vanderstichele; Jennifer Anne Doherty; et al. (Human Genetics, 2016)

Warfare in stingless bees - C. Grüter; L. G. von Zuben; F. H. I. D. Segers; J. P. Cunningham (Insectes Sociaux, 2016)

Serosurvey of canine distemper virus and canine parvovirus in wild canids and domestic dogs at the rural interface in the Coquimbo Region, Chile - G. Acosta-Jamett; A. A. Cunningham; B. M. deC. Bronsvoort; S. Cleaveland (European Journal of Wildlife Research, 2015)

Candidate locus analysis of the TERT–CLPTM1L cancer risk region on chromosome 5p15 identifies multiple independent variants associated with endometrial cancer risk - Luis G. Carvajal-Carmona; Tracy A. O’Mara; Jodie N. Painter; Felicity A. Lose; Joe Dennis; Kyriaki Michailidou; Jonathan P. Tyrer; Shahana Ahmed; Kaltin Ferguson; Catherine S. Healey; Karen Pooley; Jonathan Beesley; et al. (Human Genetics, 2015)

Genome-wide association study of subtype-specific epithelial ovarian cancer risk alleles using pooled DNA - Madalene A. Earp; Linda E. Kelemen; Anthony M. Magliocco; Kenneth D. Swenerton; Georgia Chenevix-Trench; Yi Lu; Alexander Hein; Arif B. Ekici; Matthias W. Beckmann; Peter A. Fasching; Diether Lambrechts; Evelyn Despierre; et al. (Human Genetics, 2014)

Observed decline of the Atlantic meridional overturning circulation 2004–2012 - D. A. Smeed; G. D. McCarthy; S. A. Cunningham; E. Frajka-Williams; D. Rayner; W. E. Johns; C. S. Meinen; M. O. Baringer; B. I. Moat; A. Duchez; H. L. Bryden (Ocean Science, 2014)
The Atlantic meridional overturning circulation (AMOC) has been observed continuously at 26° N since April 2004. The AMOC and its component parts are monitored by combining a transatlantic array of moored instruments with submarine-cable-based measurements of the Gulf Stream and satellite derived Ekman transport. The time series has recently been extended to October 2012 and the results show a downward trend since 2004. From April 2008 to March 2012, the AMOC was an average of 2.7 Sv (1 Sv = 106 m3 s−1) weaker than in the first four years of observation (95% confidence that the reduction is 0.3 Sv or more). Ekman transport reduced by about 0.2 Sv and the Gulf Stream by 0.5 Sv but most of the change (2.0 Sv) is due to the mid-ocean geostrophic flow. The change of the mid-ocean geostrophic flow represents a strengthening of the southward flow above the thermocline. The increased southward flow of warm waters is balanced by a decrease in the southward flow of lower North Atlantic deep water below 3000 m. The transport of lower North Atlantic deep water slowed by 7% per year (95% confidence that the rate of slowing is greater than 2.5% per year).

A global quantitative synthesis of local and landscape effects on wild bee pollinators in agroecosystems - Christina M. Kennedy; Eric Lonsdorf; Maile C. Neel; Neal M. Williams; Taylor H. Ricketts; Rachael Winfree; Riccardo Bommarco; Claire Brittain; Alana L. Burley; Daniel Cariveau; Luísa G. Carvalheiro; Natacha P. Chacoff; et al. (Ecology Letters, 2013)
Bees provide essential pollination services that are potentially affected both by local farm management and the surrounding landscape. To better understand these different factors, we modelled the relative effects of landscape composition (nesting and floral resources within foraging distances), landscape configuration (patch shape, interpatch connectivity and habitat aggregation) and farm management (organic vs. conventional and local‐scale field diversity), and their interactions, on wild bee abundance and richness for 39 crop systems globally. Bee abundance and richness were higher in diversified and organic fields and in landscapes comprising more high‐quality habitats; bee richness on conventional fields with low diversity benefited most from high‐quality surrounding land cover. Landscape configuration effects were weak. Bee responses varied slightly by biome. Our synthesis reveals that pollinator persistence will depend on both the maintenance of high‐quality habitats around farms and on local management practices that may offset impacts of intensive monoculture agriculture.

Performance evaluation of a new fourth-generation HIV combination antigen–antibody assay - A. Mühlbacher; H. Schennach; J. van Helden; T. Hebell; G. Pantaleo; P. Bürgisser; C. Cellerai; P. Permpikul; M. I. Rodriguez; A. Eiras; F. Alborino; P. Cunningham; et al. (Medical Microbiology and Immunology, 2013)

Generation of Priority Research Questions to Inform Conservation Policy and Management at a National Level - MURRAY A. RUDD; KAREN F. BEAZLEY; STEVEN J. COOKE; ERICA FLEISHMAN; DANIEL E. LANE; MICHAEL B. MASCIA; ROBIN ROTH; GARY TABOR; JISELLE A. BAKKER; TERESA BELLEFONTAINE; DOMINIQUE BERTEAUX; BERNARD CANTIN; et al. (Conservation Biology, 2011)
Integrating knowledge from across the natural and social sciences is necessary to effectively address societal tradeoffs between human use of biological diversity and its preservation. Collaborative processes can change the ways decision makers think about scientific evidence, enhance levels of mutual trust and credibility, and advance the conservation policy discourse. Canada has responsibility for a large fraction of some major ecosystems, such as boreal forests, Arctic tundra, wetlands, and temperate and Arctic oceans. Stressors to biological diversity within these ecosystems arise from activities of the country's resource‐based economy, as well as external drivers of environmental change. Effective management is complicated by incongruence between ecological and political boundaries and conflicting perspectives on social and economic goals. Many knowledge gaps about stressors and their management might be reduced through targeted, timely research. We identify 40 questions that, if addressed or answered, would advance research that has a high probability of supporting development of effective policies and management strategies for species, ecosystems, and ecological processes in Canada. A total of 396 candidate questions drawn from natural and social science disciplines were contributed by individuals with diverse organizational affiliations. These were collaboratively winnowed to 40 by our team of collaborators. The questions emphasize understanding ecosystems, the effects and mitigation of climate change, coordinating governance and management efforts across multiple jurisdictions, and examining relations between conservation policy and the social and economic well‐being of Aboriginal peoples. The questions we identified provide potential links between evidence from the conservation sciences and formulation of policies for conservation and resource management. Our collaborative process of communication and engagement between scientists and decision makers for generating and prioritizing research questions at a national level could be a model for similar efforts beyond Canada.

Impact of hydrographic data assimilation on the modelled Atlantic meridional overturning circulation - G. C. Smith; K. Haines; T. Kanzow; S. Cunningham (Ocean Science, 2010)
Here we make an initial step toward the development of an ocean assimilation system that can constrain the modelled Atlantic Meridional Overturning Circulation (AMOC) to support climate predictions. A detailed comparison is presented of 1° and 1/4° resolution global model simulations with and without sequential data assimilation, to the observations and transport estimates from the RAPID mooring array across 26.5° N in the Atlantic. Comparisons of modelled water properties with the observations from the merged RAPID boundary arrays demonstrate the ability of in situ data assimilation to accurately constrain the east-west density gradient between these mooring arrays. However, the presence of an unconstrained "western boundary wedge" between Abaco Island and the RAPID mooring site WB2 (16 km offshore) leads to the intensification of an erroneous southwards flow in this region when in situ data are assimilated. The result is an overly intense southward upper mid-ocean transport (0–1100 m) as compared to the estimates derived from the RAPID array. Correction of upper layer zonal density gradients is found to compensate mostly for a weak subtropical gyre circulation in the free model run (i.e. with no assimilation). Despite the important changes to the density structure and transports in the upper layer imposed by the assimilation, very little change is found in the amplitude and sub-seasonal variability of the AMOC. This shows that assimilation of upper layer density information projects mainly on the gyre circulation with little effect on the AMOC at 26° N due to the absence of corrections to density gradients below 2000 m (the maximum depth of Argo). The sensitivity to initial conditions was explored through two additional experiments using a climatological initial condition. These experiments showed that the weak bias in gyre intensity in the control simulation (without data assimilation) develops over a period of about 6 months, but does so independently from the overturning, with no change to the AMOC. However, differences in the properties and volume transport of North Atlantic Deep Water (NADW) persisted throughout the 3 year simulations resulting in a difference of 3 Sv in AMOC intensity. The persistence of these dense water anomalies and their influence on the AMOC is promising for the development of decadal forecasting capabilities. The results suggest that the deeper waters must be accurately reproduced in order to constrain the AMOC.

Clear and independent associations of several HLA-DRB1 alleles with differential antibody responses to hepatitis B vaccination in youth - Yufeng Li; Rong Ni; Wei Song; Wenshuo Shao; Sadeep Shrestha; Sushma Ahmad; Coleen K. Cunningham; Patricia M. Flynn; Bill G. Kapogiannis; Craig M. Wilson; Jianming Tang (Human Genetics, 2009)

Resource allocation in a social wasp: effects of breeding system and life cycle on reproductive decisions - ELIZABETH L. JOHNSON; TYLER W. CUNNINGHAM; SARAH M. MARRINER; JENNIFER L. KOVACS; BRENDAN G. HUNT; DIMPAL B. BHAKTA; MICHAEL A. D. GOODISMAN (Molecular Ecology, 2009)
Organisms must make important decisions on how to allocate resources to reproduction. We investigated allocation decisions in the social wasp Vespula maculifrons to understand how social insects make reproductive choices. We first determined how annual colonies apportioned resources to growth and reproduction by analysing developing brood. In contrast to expectations, colonies invested in both growth (workers) and reproduction (males) simultaneously. In addition, colonies showed evidence of producing males in pulses and reversing their reproductive choices by decreasing investment in males late in the season. This reversal is consistent with theory suggesting that colonies decrease production in males if fitness of late emerging males is low. To further investigate reproductive decisions within colonies, we determined if the male mates of multiply‐mated queens varied in their reproductive success over time. Sperm use by queens did vary over time suggesting that male success may depend on sperm clumping within the female reproductive tract. Finally, we tested if colony sex ratio conformed to expectations under kin selection theory that nestmate relatedness would positively correlate with investment in new queens if workers controlled sex allocation. Surprisingly, the proportion of queens produced by colonies was negatively correlated with nestmate relatedness, suggesting that allocation may be shaped by advantages arising from increased genetic diversity resulting from multiple mating by queens. Overall, our study suggests that the reproductive decisions of colonies are flexible and may depend both on environmental cues arising from energetic needs of the colony and genetic cues arising from mating behaviours of queens.

Characterisation of the European Marine Sites in South West England: The Fal and Helford Candidate Special Area of Conservation (cSAC) - W. J. Langston; B. S. Chesman; G. R. Burt; M. Taylor; R. Covey; N. Cunningham; P. Jonas; S. J. Hawkins (Hydrobiologia, 2006)

Phosphate nutrition effects on growth, phosphate transporter transcript levels and physiology of alfalfa cells - S. F. Abu. Qamar; T. G. Sors; S. M. Cunningham; B. C. Joern; J. J. Volenec (Plant Cell, Tissue and Organ Culture (PCTOC), 2005)

Patterns of fish deformities and their association with trematode cysts in the Willamette River, Oregon - Michael E. Cunningham; Douglas F. Markle; Virginia G. Watral; Michael L. Kent; Larry R. Curtis (Environmental Biology of Fishes, 2005)

Vulnerability of mouse cortical neurons to doxorubicin-induced apoptosis is strain-dependent and is correlated with mRNAs encoding Fas, Fas-Ligand, and metalloproteinases - M. Wetzel; J. Tibbitts; G. A. Rosenberg; L. A. Cunningham (Apoptosis, 2004)

Letters - S.C. Allen; G. Cunningham; J.H. Farrell; D.I. Dickmann (Journal of Forestry, 2003)

Reduced ethanol-induced conditioned taste aversion and conditioned place preference in GIRK2 null mutant mice - Katherine G. Hill; Herminia Alva; Yuri A. Blednov; Christopher L. Cunningham (Psychopharmacology, 2003)

Factors affecting the presence of the cool temperate rain forest tree myrtle beech ( Nothofagus cunninghamii ) in southern Australia: integrating climatic, terrain and disturbance predictors of distribution patterns - D. B. Lindenmayer; B. G. Mackey; R. B. Cunningham; C. F. Donnelly; I. C. Mullen; M. A. McCarthy; A. M. Gill (Journal of Biogeography, 2000)
Aim This study identified the factors influencing the presence, stocking rate and basal area of the southern Australian cool temperate rain forest tree myrtle beech ( Nothofagus cunninghamii ). Location This investigation was conducted in the montane ash forests of the Central Highlands of Victoria, south‐eastern Australia. Methods The occurrence of N. cunninghamii was measured as part of field surveys of 474 sites (2844 plots) distributed widely throughout mountain ash ( Eucalyptus regnans ), alpine ash ( E. delegatensis ) and shining gum ( E. nitens ) forests. Statistical analysis was employed to examine relationships between the occurrence of N. cunninghamii and measured site attributes and interpolated and derived environmental variables. Results The presence of N. cunninghamii was significantly related to five variables: the age of the overstorey eucalypt stand, dominant species of overstorey eucalypt tree, topographic position in the landscape, slope and the estimated quantity of precipitation in the warmest quarter of the year. N. cunninghamii was more likely to occur in old growth eucalypt stands, in gullies and locations with high values for rainfall in the warmest quarter. In addition, there was an interaction between slope and dominant eucalypt tree species—in forests dominated by E. regnans , N. cunninghamii was more likely to occur on steep slopes whereas in E. nitens and E. delegatensis ‐dominated stands, N. cunninghamii was more likely to occur on flatter terrain. Statistical modelling also showed a significant positive effect of slope on both the stocking rate and basal area of the species. The stocking rate of N. cunninghamii also was significantly higher in old growth eucalypt stands. Main conclusions The study demonstrated that the patterns of distribution of N. cunninghamii may be more complex than recognized previously and it illustrated the importance of multiple factors including climatic conditions, disturbance processes (as reflected through the age of the dominant overstorey eucalypt stands) and topography. Our work also shows there can be complex interactions between age cohorts of different tree species in the same stand—in this case, the dominant overstorey eucalypts and the understorey which includes N. cunninghamii stems.

Reply to the comment by C.S. Spirakis - C. G. Cunningham; J. D. Rasmussen; T. A. Steven; R. O. Rye; P. D. Rowley; S. B. Romberger; J. Selverstone (Mineralium Deposita, 1999)

Dissipation of Phloxine B and Uranine in Protein Bait Sprayed in a Coffee Field for the Suppression of Mediterranean Fruit Fly - J. P. Alcantara-Licudine; R. T. Cunningham; N. J. Liquido; G. T. McQuate; Q. X. Li (Bulletin of Environmental Contamination and Toxicology, 1999)

Hydrothermal uranium deposits containing molybdenum and fluorite in the Marysvale volcanic field, west-central Utah - C. G. Cunningham; J. D. Rasmussen; T. A. Steven; R. O. Rye; P. D. Rowley; S. B. Romberger; J. Selverstone (Mineralium Deposita, 1998)

The carcinogenicity of diethylstilbestrol: structural evidence for a non-genotoxic mechanism - A. Cunningham; G. Klopman; H. S. Rosenkranz (Archives of Toxicology, 1996)

Portage: A new early-maturing, round white table potato variety - A. F. Reeves; G. A. Porter; C. E. Cunningham; R. J. Nickeson; F. E. Manzer; T. M. Work; A. A. Davis; E. S. Plissey (American Journal of Potato Research, 1995)

Prestile: A new round white potato variety - A. F. Reeves; G. A. Porter; C. E. Cunningham; R. J. Nickeson; F. E. Manzer; T. M. Work; A. A. Davis; E. S. Plissey (American Journal of Potato Research, 1994)

Chronic effects of ingested asbestos in rats - H. M. Cunningham; C. A. Moodie; G. A. Lawrence; R. D. Pontefract (Archives of Environmental Contamination and Toxicology, 1977)

Biochemical characterization of six trisomics of grain sorghum, Sorghum bicolor (L.) Moench - H. W. Suh; D. R. Goforth; Bryce A. Cunningham; G. H. Liang (Biochemical Genetics, 1977)

Book reviews - Seymour G. Gilbert; Charles Cunningham (American Journal of Potato Research, 1970)

Replication and cytopathogenicity of avian infectious bronchitis virus in chicken embryo kidney cells - T. G. Akers; C. H. Cunningham (Archives of Virology, 1968)

s of papers presented at the 50th Anniversary Meeting of The Potato Association of America and 13th National Potato Utilization Conference Perkins Inn, Riverhead, New York July 15, 16, 17, 18, 1963 - Glenn D. Boyd; Calderon Peter; Ora Smith; L. R. Mattick; John C. Campbell; R. C. Cetas; Carl O. Davis; Smith Ora; C. H. Dearborn; F. H. Drazga; R. K. Eskew; F. B. Talley; et al. (American Journal of Potato Research, 1963)

Minutes of Executive Committee Meeting, Annual Business Meeting, Committee reports and Financial Report - L. C. Young; Richard L. Sawyer; Hugh J. Murphy; J. W. Scannell; John C. Campbell; Walter C. Sparks; Ora Smith; William B. Raymer; R. H. Treadway; J. C. Campbell; Arthur Hawkins; R. G. Rowberry; et al. (American Journal of Potato Research, 1962)

Effect of size of plot, experimental design and replication on efficiency of potato fertilizer experiments - G. L. Terman; Mildred R. Covell; C. E. Cunningham (American Journal of Potato Research, 1957)

Effect of date and method of kill on yield, specific gravity and other quality factors of maine potatoes - G. L. Terman; C. E. Cunningham; Michael Goven (American Journal of Potato Research, 1952)

Effect of storage temperature and size on French fry quality, shrinkage and specific gravity of Maine potatoes - G. L. Terman; Michael Goven; C. E. Cunningham (American Journal of Potato Research, 1950)